Measuring readiness, acceptance and satisfaction of innovative digital economy: preliminary findings - Hazita Azman; Ali Salman; Supyan Hussin; Norizan Abdul Razak; Mohd Safar Hashim; Musa Abu Hassan; Samsinar Md Sidin; Rozhan Mohamed Idrus; Mohammad Radzi Manap; Satirah Ahmad (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
The paper addresses the need to investigate the social, cultural, and consumer environmental factors that help build a conducive digital ecosystem to enhance Malaysia’s national competitiveness in the Digital economy while using technology to enhance societal well-being and wealth creations opportunities. This paper aims at determining the readiness and level of acceptance of current and proposed applications considered as constructs used in creating and validating Critical Success Factors Framework for innovative digital economy. This study employs quantitative method utilizing a set of questionnaire distributed to 50 respondents in Klang Valley. Convenient sampling technique was used as the selection method. However, to ensure a better representative, respondents are grouped into three different clusters based on age. The findings of this paper are derived from a pilot study conducted among 50 respondents. The findings indicate that the majority of the respondents are actively engaged in online transaction. As far as social networking is concerned, the data show that all the respondents are using internet for email, followed by social media activities (90%). Also email and social media are the most common facilities used by the respondents. Findings also show that majority of the respondents were satisfied with the technological advancement of ICT gadgets, internet speed and the quality of website contents. More initiatives such as tax reduction in digital gadgets, tax deduction in acquiring digital gadgets for every household, digital entrepreneurship training programs for marginalized communities, and legal advices to support people’s digital economy activities should be provided by authorities including government linked agencies (GLC).